(x^2 - x - 12) = (x^2 - 4x + 3x -12) = x(x -4) + 3(x -4) = (x-3) x (x-4)
Hence (x^2 - x - 12) divided by (x -4) is (x-3)
Divide all terms by 4:- x2+7x+12 = (x+3)(x+4) when factored
x3 + 3x2 - 4x -12 x2(x + 3) - 4(x + 3) (x2 - 4)(x+3)
x²-x-12=0 x1=-(-1/2) - Square root of ((-1/2)²+12) x1=0.5 - 3.5 x1=-3 x2=-(-1/2) + Square root of ((-1/2)²+12) x2=0.5 + 3.5 x2=4
If you mean: x squared -7x +12 then it is (x-3)(x-4) when factored
Divide both sides of the equation by x: x2 = 9x x2 / x = 9x / x x = 9
(x2-x-12)/(x-4) = (x+3)
x2 - x - 12First try and factor that expression.Notice that it happens to be the product of (x - 4) and (x + 3). This makes your problem easy.(x2 - x - 12) / (x - 4)= (x - 4) (x + 3) / (x - 4)Now just divide numerator and denominator by the common factor. ("Cancel" (x - 4) out of numerator and denominator.)Wind up with the answer = (x + 3)
14
x2 - x - 12 = 0 ∴ (x + 3)(x - 4) = 0 ∴ x ∈ {-3, 4}
x2 + x - 12 = (x + 4)(x - 3)
14
If: x2+x = 12 Then: x2+x-12 = 0 And using the quadratic formula: x = -4 or x = 3
If that's x2, the answer is (x - 5)(x - 4)
-10
4 x 2 + 4 = 12 x = 4
Divide all terms by 4:- x2+7x+12 = (x+3)(x+4) when factored
x2-7x+12 (x-3)(x-4)